The Streptochaeta Genome and the Evolution of the Grasses - Seetharam, Arun S.; Yu, Yunqing; Bélanger, Sébastien; Clark, Lynn G.; Meyers, Blake C.; Kellogg, Elizabeth A.; Hufford, Matthew B. (Frontiers in Plant Science, 2021)
In this work, we sequenced and annotated the genome of Streptochaeta angustifolia, one of two genera in the grass subfamily Anomochlooideae, a lineage sister to all other grasses. The final assembly size is over 99% of the estimated genome size. We find good collinearity with the rice genome and have captured most of the gene space. Streptochaeta is similar to other grasses in the structure of its fruit (a caryopsis or grain) but has peculiar flowers and inflorescences that are distinct from those in the outgroups and in other grasses. To provide tools for investigations of floral structure, we analyzed two large families of transcription factors, AP2-like and R2R3 MYBs, that are known to control floral and spikelet development in rice and maize among other grasses. Many of these are also regulated by small RNAs. Structure of the gene trees showed that the well documented whole genome duplication at the origin of the grasses (ρ) occurred before the divergence of the Anomochlooideae lineage from the lineage leading to the rest of the grasses (the spikelet clade) and thus that the common ancestor of all grasses probably had two copies of the developmental genes. However, Streptochaeta (and by inference other members of Anomochlooideae) has lost one copy of many genes. The peculiar floral morphology of Streptochaeta may thus have derived from an ancestral plant that was morphologically similar to the spikelet-bearing grasses. We further identify 114 loci producing microRNAs and 89 loci generating phased, secondary siRNAs, classes of small RNAs known to be influential in transcriptional and post-transcriptional regulation of several plant functions.